A joint ERS/ATS policy statement: what constitutes an adverse health effect of air pollution? An analytical framework. Issue 1 (12th January 2017) - Thurston, George D.; Kipen, Howard; Annesi-Maesano, Isabella; Balmes, John; Brook, Robert D.; Cromar, Kevin; De Matteis, Sara; Forastiere, Francesco; Forsberg, Bertil; Frampton, Mark W.; Grigg, Jonathan; Heederik, Dick; et al.
The American Thoracic Society has previously published statements on what constitutes an adverse effect on health of air pollution in 1985 and 2000. We set out to update and broaden these past statements that focused primarily on effects on the respiratory system. Since then, many studies have documented effects of air pollution on other organ systems, such as on the cardiovascular and central nervous systems. In addition, many new biomarkers of effects have been developed and applied in air pollution studies. This current report seeks to integrate the latest science into a general framework for interpreting the adversity of the human health effects of air pollution. Rather than trying to provide a catalogue of what is and what is not an adverse effect of air pollution, we propose a set of considerations that can be applied in forming judgments of the adversity of not only currently documented, but also emerging and future effects of air pollution on human health. These considerations are illustrated by the inclusion of examples for different types of health effects of air pollution. Air pollution has many effects on health; this document provides guidance to judge the adversity of such effects http://ow.ly/T2xx304WTZp